Characteristics of Prognostic Programmed Cell Death–Related Long Noncoding RNAs Associated With Immune Infiltration and Therapeutic Responses to Colon Cancer - Chen, Yan; Zhang, Yue; Lu, Jiayi; Liu, Zhongchen; Zhao, Shasha; Zhang, Mengmei; Lu, Mingzhi; Xu, Wen; Sun, Fenyong; Wu, Qi; Zhong, Qi; Cui, Zhongqi (Frontiers in Immunology, 2022)
Programmed cell death (PCD) plays an important role in the onset and progression of various cancers. The molecular events surrounding the occurrence of abnormally expressed long noncoding RNAs (lncRNAs) leading to colon cancer (CC) have become a focus. We comprehensively evaluated the roles of PCD-related lncRNAs in the clinical management of CC and their immune responses. Therefore, we screened 41 prognostic PCD-related lncRNAs in The Cancer Genome Atlas database using co-expression analysis and assigned patients to groups according to the results of cluster analysis. The immune response and functions of cluster 2 were substantially suppressed, which might explain the poor prognosis in this group. A prognostic model comprising eight PCD-related lncRNAs was developed, and its effectiveness was verified using an external database. High-and low-risk groups had different epigenetic modifications and changes in immune cell infiltration. Patients in the high-risk group were resistant to immunotherapy and various chemotherapeutic drugs. Studies in vitro and in vivo further confirmed a carcinogenic role of the lncRNA U62317.4. Our findings of the prognostic value of PCD-related lncRNAs revealed their important roles in immune response disorders, thus providing valuable insights into the clinical management and molecular mechanisms of CC.